Implementasi Fungsi Pendidikan Politik Partai Politik terhadap Generasi Z Berdasarkan UU No. 2 Tahun 2011: Studi pada DPC Partai Gerindra Kota Padang - Silvira, Silvira; Mubarak, Adil (Lembaga Yasin AlSys, 2025)
This study is motivated by the low political participation of Generation Z in the lead-up to the 2024 regional elections (Pilkada), despite political education being one of the core functions of political parties aimed at fostering public engagement in democratic processes. The research seeks to explore the effectiveness of political education programs—such as outreach activities and workshops—in raising political awareness and addressing challenges such as distrust in political institutions and limited access to digital information. A qualitative descriptive method was employed, utilizing interviews, observation, and documentation. Informants included members of the Padang City Branch Leadership Council (DPC) of the Gerindra Party, representatives from the National and Political Unity Agency (Kesbangpol), and individuals from Generation Z who were the target of political education efforts. The findings indicate that political education initiatives by the Gerindra Party remain limited and have not yet yielded optimal results. Over the past year, activities have included only two main agendas: internal cadre meetings and social events such as Independence Day celebrations and screenings of the film G30S/PKI. These activities primarily focused on internal development and lacked strategic outreach to the broader public, particularly Generation Z, who represent a key segment of first-time voters. These findings underscore the need for innovative and expanded political education strategies that are more inclusive, structured, and adaptive to the characteristics of the digital generation, in order to enhance youth political participation in regional elections.